The influence of education packages on adequacy of breast milk and baby weight gains during the covid-19 pandemic - Nur Elly; Demsa Simbolon; Iin Nilawati (Alma Ata University Press, 2021)
Background: The process of breastfeeding in the early days of a baby's life often fails due to a lack of breast milk production. Breastfeeding education is an effort that needs to be done to prevent and overcome breastfeeding failure. During the COVID-19 pandemic, education for pregnant and postpartum women is needed that can be done online. Objectives: The purpose of this study was to determine the effectiveness of the